Portal Hypertansive Gastropathy and Helicobacter Pylori: An Endoscopic and Histopathologic Study - Ülkü SARITAŞ; Korel YALMAN; Uğur YILMAZ; Mehmet KARAHAN; Aysel ÜLKER; Vedia MÜFTÜOĞLU; Tülin ŞAHİN and Leziz ONARAN (Turkish Journal of Gastroenterology, 2020)
-